METABOLIC POLYORGANIC DISORDERS IN RATS WITH INSULIN RESISTANCE ON THE BACKGROUND OF IODINE DEFICIENCY - Guranych, S.P.; Tsymbala, E.M.; Stetseviat, V.B.; Todoriv, T.V.; Danyliuk, I.M.; Guranych, T.V.; Voronych-Semchenko, N.M. (World of Medicine and Biology, 2021)
Impaired glucose tolerance leads to structural and functional restructuring of internal organs, that intensify under iodine deficiency conditions. Studies were carried on male rats (animals with insulin resistance under conditions of adequate iodine supply and iodine deficiency). Metabolic changes were studied in blood serum, homogenates of kidneys, heart, liver, teeth pulp and oral mucosa. It is established that development of insulin resistance is accompanied by activation of lipoperoxidation processes in studied organs, decrease of catalase activity and increased glutathione defense system. In animals signs of visceral obesity are developed, manifested by increase of atherogenic index and leptin level, decrease of ghrelin concentration in blood serum. Under conditions of combined endocrinopathy increase of lipoperoxide products in tissues on the background of antioxidant reserve inhibition, growth of proatherogenic lipid fractions relative to data in animals with isolated insulin resistance are observed, that reflects potentiation of pathological changes under conditions of combined endocrinopathy.